2012
DOI: 10.1111/j.1547-5069.2012.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences Regarding Informal Caregivers of Older People

Abstract: These findings support the following recommendations regarding nursing interventions: (a) nurses should take into account specific cultural patterns in caregiving to improve their understanding concerning the relationships between gender and intensity of care, and (b) gender should be taken into account in interventions that are tailored toward addressing subjective burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 36 publications
4
45
1
6
Order By: Relevance
“…), but the evidence for gender differences is limited (Del‐Pino‐Casado et al . ). There is more evidence to support differential negative impacts.…”
Section: Discussionmentioning
confidence: 97%
“…), but the evidence for gender differences is limited (Del‐Pino‐Casado et al . ). There is more evidence to support differential negative impacts.…”
Section: Discussionmentioning
confidence: 97%
“…Ekwall, Sivberg, and Hallberg () found that male caregivers were more satisfied than female caregivers. Balanced reciprocity, reported to be higher in male caregivers, in the caregiver–recipient relationship was also found to have a protective effect on the caregiver burden (del‐Pino‐Casado, Frías‐Osuna, Palomino‐Moral, & Ramón Martínez‐Riera, ). It is, therefore, important that healthcare providers pay attention to resources that can maintain or further enhance a good relationship between caregiver and care recipient, especially in where the care recipient shows disturbed behaviour.…”
Section: Discussionmentioning
confidence: 98%
“…6 Due to social norms, 75-80% of the responsibility for taking care of the elderly is assumed by women. [7][8][9] It has been suggested that there are several social and cultural demands on women to adopt the role of a caregiver within the family. 6 While caregiving provides a suitable care and supportive environment for older adults, changes in the lives of these caregiving family members also affect their health.…”
Section: Introductionmentioning
confidence: 99%